THE IMPORTANCE OF LISTENING COMPREHENSION IN LEARNING ENGLISH - Sultonmurodov, Nodirbek (Журнал иностранных языков и лингвистики, 2023)
Language is a main tool of communication and it is confirmed as a connection of human being. However, communication does not include only speaking, but also listening that is the way to understand and feel how the conversation or relationships going on. According to statistics, almost billion people use English as a communicative language on a daily life and it has already entered to every field of the society. It has become a universal language and it shows that degree of requirements of learning English by people, no matter the youth, adults or senior is increasing dramatically.